The Principles of Experimental Research. - Srinagesh, K. (Elsevier, 2005)
The need to understand how to design and set up an investigative experiment is universal to students. This book offers introduction to the tools needed, including an understanding of logical processes, how to use measurement, the dos and donts of designing experiments so as to achieve reproducible results.